The diagnostic value of symptoms for colorectal cancer in primary care: a systematic review - Astin, Margaret; Griffin, Tom; Neal, Richard D; Rose, Peter; Hamilton, William (British journal of general practice, 2011)
Over 37,000 new colorectal cancers are diagnosed in the UK each year. Most present symptomatically to primary care. To conduct a systematic review of the diagnostic value of symptoms associated with colorectal cancer. Systematic review. MEDLINE, Embase, Cochrane Library, and CINAHL were searched to February 2010, for diagnostic studies of symptomatic adult patients in primary care. Studies of asymptomatic patients, screening, referred populations, or patients with colorectal cancer recurrences, or with fewer than 100 participants were excluded. The target condition was colorectal cancer. Data were extracted to estimate the diagnostic performance of each symptom or pair of symptoms. Data were pooled in a meta-analysis. The quality of studies was assessed with the QUADAS tool. Twenty-three studies were included. Positive predictive values (PPVs) for rectal bleeding from 13 papers ranged from 2.2% to 16%, with a pooled estimate of 8.1% (95% confidence interval [CI] = 6.0% to 11%) in those aged ≥ 50 years. Pooled PPV estimates for other symptoms were: abdominal pain (three studies) 3.3% (95% CI = 0.7% to 16%); and anaemia (four studies) 9.7% (95% CI = 3.5% to 27%). For rectal bleeding accompanied by weight loss or change in bowel habit, pooled positive likelihood ratios (PLRs) were 1.9 (95% CI = 1.3 to 2.8) and 1.8 (95% CI = 1.3 to 2.5) respectively, suggesting higher risk when both symptoms were present. Conversely, the PLR was one or less for abdominal pain, diarrhoea, or constipation accompanying rectal bleeding. The findings suggest that investigation of rectal bleeding or anaemia in primary care patients is warranted, irrespective of whether other symptoms are present. The risks from other single symptoms are lower, though multiple symptoms also warrant investigation.